A Rare Case Of Acute Pancreatitis Cause by Newly Diagnosed Graves’ Disease: A Successful Therapeutic Option - Abubakar, Azzaki; Yusuf, Fauzi; Maghfirah, Desi; Gunawan, Andrie; Zufry, Hendra; Edward, Meutia Nailan; Ho, Khek Yu (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Acute pancreatitis is a frequent disorder whose severity level varies from mild to life-threatening. This condition is characterized by abrupt inflammation of the pancreas. A 53-year-old male was having upper right abdominal pain and epigastric pain which began four hours after hospitalization. This case highlights the complexities of managing acute pancreatitis in a patient with Graves' disease, where hyperthyroidism may worsen pancreatitis and vice versa. Graves' disease is an autoimmune disorder causing hyperthyroidism, which can complicate pancreatitis management, particularly when treated with methimazole, which has been associated with acute pancreatitis. This case suggests a potential link between untreated Graves' disease and idiopathic acute pancreatitis. In patients presenting with unexplained pancreatitis, evaluation for hyperthyroidism may be warranted. The novelty of this case lies in the exclusion of all conventional etiologies and the possible role of autoimmune thyroid disease in pancreatic inflammation.